From Apartheid to Democracy : A Case Study of Education in Post-Apartheid South Africa - Ammu, Naga Sailaja (2017)
This thesis examines the role of education age gender years of education area of living and race in the income earned by citizens of South Africa. The aim of this is to analyse how the income earned is different for the various races present in South Africa. The methods used to analyse these phenomenons are by using STATA and running a linear regression model to prove the hypothesis: that black Africans earn much less than the white race due to the level of education and the past history which has always treated the blacks as inferiors. By regressing models it was discovered that the blacks earn much less than the other races that are in South Africa and especially the females. The information presented in this paper can be useful to future researchers NGOs in South Africa or the ones helping to make things better in that nation.